A validated prognostic classifier for V600EBRAF-mutated metastatic colorectal cancer: the 'BRAF BeCool' study. (September 2019) - Loupakis, Fotios; Intini, Rossana; Cremolini, Chiara; Orlandi, Armando; Sartore-Bianchi, Andrea; Pietrantonio, Filippo; Pella, Nicoletta; Spallanzani, Andrea; Dell'Aquila, Emanuela; Scartozzi, Mario; De Luca, Emmanuele; Rimassa, Lorenza; et al.
Abstract: Background: Despite the well-known negative prognostic value of the V600E BRAF mutation in patients with metastatic colorectal cancer (mCRC), its outcome is quite heterogeneous, and the basis for this prognostic heterogeneity should be better defined. Methods: Two large retrospective series of V600E BRAF -mutated mCRC from 22 institutions served as an exploratory and validation set to develop a prognostic score. The model was internally and externally validated. Results: A total of 395 V600E BRAF -mutated mCRCs were included in the exploratory set. Performance status, CA19.9, lactate dehydrogenase, neutrophil/lymphocyte ratio, grading and liver, lung and nodal involvement emerged as independent prognostic factors for overall survival (OS). Two different scoring systems were built: a 'complete' score (0–16) including all significant covariates and a 'simplified' score (0–9), based only on clinicopathological covariates, and excluding laboratory values. Adopting the complete score, proportions of patients with a low (0–4), intermediate (5–8) and high (9–16) score were 44.7%, 42.6% and 12.6%, respectively. The median OS was 29.6, 15.5 (hazard ratio [HR] for intermediate vs low risk: 2.16, 95% confidence interval [CI]: 1.44–3.22, p < .001) and 6.6 months (HR for high vs low risk: 4.72, 95% CI: 2.72–8.20, p < .001). Similar results were observed also after adjusting for the type of first-line treatment and adopting the simplified score. The simplified prognostic score derived from the exploratory set was then applied to the validation set for external confirmation. Conclusions: These scoring systems are based on easy-to-collect data and defined specific subgroups with relevant differences in their life expectancy. These tools could be useful in clinical practice, would allow better stratification of patients in clinical trials and may be adopted for proper adjustments in exploratory translational analyses. Highlights: The V600E BRAF mutation occurs in roughly 10% of metastatic colorectal cancer (mCRC). It leads to a peculiar clinicopathological phenotype and worse prognosis. Nevertheless, great heterogeneity in the outcome is evident among BRAF-mutated mCRC. The present study developed and validated prognostic classifiers for BRAF-mutated mCRC. These data are informative for clinical, methodological and translational purposes.